2005
DOI: 10.5194/angeo-23-2465-2005
|View full text |Cite
|
Sign up to set email alerts
|

Polar heating in Saturn's thermosphere

Abstract: Abstract.A 3-D numerical global circulation model of the Kronian thermosphere has been used to investigate the influence of polar heating. The distributions of temperature and winds resulting from a general heat source in the polar regions are described. We show that both the total energy input and its vertical distribution are important to the resulting thermal structure. We find that the form of the topside heating profile is particularly important in determining exospheric temperatures. We compare our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…This is consistent with recent results for Saturn (Smith et al, 2005b;Müller-Wodarg et al, 2006;Smith et al, 2007). Even when we added enough high latitude heating to raise the polar temperature to 1500 K -slightly in excess of the observations -the equatorial temperature was still low, in the region of 400 K. Figure 16 shows a comparison between temperature profiles predicted by our model and the Galileo probe temperature profile (Seiff et al, 1998).…”
Section: Thermospheresupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with recent results for Saturn (Smith et al, 2005b;Müller-Wodarg et al, 2006;Smith et al, 2007). Even when we added enough high latitude heating to raise the polar temperature to 1500 K -slightly in excess of the observations -the equatorial temperature was still low, in the region of 400 K. Figure 16 shows a comparison between temperature profiles predicted by our model and the Galileo probe temperature profile (Seiff et al, 1998).…”
Section: Thermospheresupporting
confidence: 79%
“…Similar high temperatures are present in Saturn's thermosphere, and recent studies have attempted to explain these measurements by the redistribution of high latitude heating. Smith et al (2005b) found that an arbitrary high latitude source of thermal energy did generate sufficient redistributive winds to reproduce the observed temperatures, but the more sophisticated calculations of Smith et al (2007) showed that when high-latitude energy inputs of Joule heating and ion drag were included, poleward meridional winds were generated that cooled, rather than heated, low latitudes.…”
mentioning
confidence: 99%
“…In turn, this would correspond to a cooling rate of 7.8 × 10 12 W for the whole column above the homopause, or 3.2 × 10 12 W for the column above the main H + 3 emission layer. This is a highly significant rate, and corresponds to the kind of heating rates produced in Saturn's polar upper atmosphere by Joule heating and ion drag [24].…”
Section: Cassini Measurements Of the Aurora Of Saturnmentioning
confidence: 93%
“…The above considerations enable more detailed vertical profiles of the thermosphere to be developed. These are shown below for Jupiter ( Figure 3; Grodent et al, 2001) and for Saturn (Figure 4;Smith et al, 2004). They show that, except at the very bottom of the thermosphere, where hydrocarbon molecules still have some abundance, the atmosphere is composed mainly of molecular and atomic hydrogen, with helium as a minor species.…”
Section: Basic Thermospheric Parametersmentioning
confidence: 94%